DESCRIPTIVE ANALYSIS OF THE WORK MOTIVATION OF STATE CIVIL APPARATUS IN THE SCOPE OF GOVERNMENT ORGANIZATION OF KUPANG CITY - Jefirstson R Riwu Kore; Fellyanus Habaora; Firda Richset Riwu Kore (Institute of Computer Science (IOCS), 2023)
The purpose of this research is to understand and determine the category of work motivation characteristics of State Civil Apparatus within the scope of the Government Secretariat of the City of Kupang, East Nusa Tenggara. This research was conducted for 6 months, from January to July 2023 using a purposive stratified proportional sampling method to 370 civil apparatus of the Kupang City Government. The types of data used are primary data and secondary data obtained by distributing questionnaires, interviews, and documentation. The data analysis used a class range table from the Likert scale analysis technique. The results showed that the work motivation of the State Civil Apparatus within the scope of the Kupang City Government is still in the medium category or tends to be socially oriented and can be an obstacle in achieving the vision and mission of regional heads or government performance. The characteristics of needs in the motivation theory that need to be maintained are security, social, and self-esteem needs, while the needs for autonomy and self-actualization need serious attention to be maximized.